The night after Christmas - Stevenson, James, 1929- (New York : Greenwillow Books, 1981)
Tossed in garbage cans after they are replaced by new toys at Christmas, a teddy bear and a doll are befriended by a stray dog.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
School Library Journal
2.4
K-3
Keywords: Teddy bears -- Fiction; Dolls -- Fiction; Toys -- Fiction; Teddy bears -- Fiction; Dolls -- Fiction; Toys -- Fiction